Service provision for young‐onset dementia in the UK. Issue 4 (10th August 2015) - Rayment, Dane; Kuruvilla, Tarun
<x xml:space="preserve">Abstract</x> In this review article, Drs Rayment and Kuruvilla look at the problems faced by younger people with dementia, the current state of care delivery in the country for young‐onset dementia (YOD), guidelines for service provision and they suggest what could improve the availability of specialised YOD services in the UK.